2015
DOI: 10.1124/dmd.114.062828
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of the SGLT2 Inhibitor Remogliflozin Etabonate in Subjects with Mild and Moderate Renal Impairment

Abstract: Remogliflozin etabonate (RE), the prodrug of remogliflozin, is an inhibitor of the sodium glucose-dependent renal transporter 2 (SGLT2), enabling urinary glucose excretion to reduce hyperglycemia for the treatment of type 2 diabetes. Renal function declines more rapidly in patients with type 2 diabetes, making it difficult or unsafe to continue on some antidiabetic therapeutics. In an initial effort to understand the potential utility of RE in patients with renal impairment, the pharmacodynamics and pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Several pharmacokinetic/pharmacodynamic studies have demonstrated that the effects of SGLT2 inhibitors on UGE and plasma glucose concentrations are attenuated by reduced renal function, especially severely reduced renal function or chronic kidney disease [ 6 , 15 18 ], consistent with our findings using 24-h CGM. Our results provide further insight into the impact of reduced renal function on the glucose-lowering effects of SGLT2 inhibitors, and that co-administration of a SGLT2 inhibitor with another antidiabetic drug, which improves postprandial glucose, might be useful for the patients with reduced renal function if improvements in glucose concentrations are not observed with monotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…Several pharmacokinetic/pharmacodynamic studies have demonstrated that the effects of SGLT2 inhibitors on UGE and plasma glucose concentrations are attenuated by reduced renal function, especially severely reduced renal function or chronic kidney disease [ 6 , 15 18 ], consistent with our findings using 24-h CGM. Our results provide further insight into the impact of reduced renal function on the glucose-lowering effects of SGLT2 inhibitors, and that co-administration of a SGLT2 inhibitor with another antidiabetic drug, which improves postprandial glucose, might be useful for the patients with reduced renal function if improvements in glucose concentrations are not observed with monotherapy.…”
Section: Discussionsupporting
confidence: 90%
“…After administration, RE is de-esterified by non-specific esterases present in mucosal cells of the gastrointestinal tract to get converted into its active form remogliflozin ( Figure 2B). 14 RE is rapidly and almost completely absorbed and available in the plasma within 10 minutes with a Tmax of 0.5-1 hour. 6 The administration with standard breakfast slightly delayed the Tmax by approximately 0.5-1.5 hours (hrs); however, there was no significant difference in the Cmax or Area under Curve (AUC) relative to the fasting state.…”
Section: Scientific Summary Pharmacokinetic (Pk)/pharmacodynamic (Pd)mentioning
confidence: 99%
“…Metabolic products of RE are eliminated from the body through renal excretion. 14 In radiolabelled absorption, metabolic, and excretion (AME) studies, approximately 93% was excreted in the urine, of which about 11% of the dose was recovered as remogliflozin in urine; the majority of drug-related material is eliminated via the urine as inactive glucuronide metabolites. 14 The inhibitory concentration of remogliflozin was evaluated, and Ki values of 12.4 and 4520 nmol/l for SGLT2 and SGLT1, respectively, were demonstrated.…”
Section: Scientific Summary Pharmacokinetic (Pk)/pharmacodynamic (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, mild to moderate renal impairment does not alter the pharmacokinetics and pharmacodynamics of RE, suggesting no dose adjustment of RE is necessary. This is an advantage of RE when compared with other SGLT2 inhibitors, including canagliflozin, dapagliflozin, and empagliflozin, where drug plasma accumulation has been shown in patients with mild to moderate renal impairment (O'Connor‐Semmes et al, ).…”
Section: Phlorizinmentioning
confidence: 99%